2020
DOI: 10.1017/wsc.2020.4
|View full text |Cite
|
Sign up to set email alerts
|

Differences in efficacy, resistance mechanism and target protein interaction between two PPO inhibitors in Palmer amaranth (Amaranthus palmeri)

Abstract: A weed survey was conducted on 134 Palmer amaranth (Amaranthus palmeri S. Watson) populations from Mississippi and Arkansas in 2017 to investigate the spread of resistance to protoporphyrinogen oxidase (PPO) inhibitors using fomesafen as a proxy. Fomesafen resistance was found in 42% of the A. palmeri populations. To investigate the resistance basis of different PPO inhibitors, we further characterized 10 representative populations by in planta bioassay in a controlled environment and molecular characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 54 publications
(74 reference statements)
1
18
0
Order By: Relevance
“…15 Protogen binding to ∆G210 PPO2 was not negatively affected, which is a favorable condition to minimize related fitness costs. 15,16 However, the same cannot be said about G399A. The authors concluded that the additional methyl group from Ala in relation to Gly protruded into the binding-site, creating repulsive interactions towards the inhibitor (and consequently, towards the substrate).…”
Section: Introductionmentioning
confidence: 99%
“…15 Protogen binding to ∆G210 PPO2 was not negatively affected, which is a favorable condition to minimize related fitness costs. 15,16 However, the same cannot be said about G399A. The authors concluded that the additional methyl group from Ala in relation to Gly protruded into the binding-site, creating repulsive interactions towards the inhibitor (and consequently, towards the substrate).…”
Section: Introductionmentioning
confidence: 99%
“…Higher ED50 values (up to 614 g fomesafen ha −1 ) were estimated for PPO-resistant populations from Kentucky carrying ∆G210 mutation [38]. On the other hand, low ED50 values (from 12.4 to 28.5 g fomesafen ha −1 ) were reported for populations from Tennessee [27]. Even with low ED50 values, these Tennessee populations had survivors when treated with up to 3360 g ha −1 fomesafen.…”
Section: Resistance Level To Fomesafen and Overall Response To Other Foliar-applied Herbicidesmentioning
confidence: 91%
“…Since A. palmeri is dioecious, it is an obligate outcrossing specie; thus, the accumulation of PPO mutations in the same plant via gene flow is expected. Indeed, some survivors of fomesafen treatment harbor ∆G210 + R128G mutations in the same plant [27]. The authors did not report the level of resistance in these plants or if the mutations co-occurred in the same allele.…”
Section: Introductionmentioning
confidence: 97%
“…It is also possible that as a simplified testing system that focuses on the target organelle of the plants (chloroplast), the leaf-disk assay is more effective in detecting target site-based resistance (TR) than non-target site based resistance (NTR). Interestingly, for the E. indica, B. scoparia, and Amaranthus populations we tested for glyphosate, dicamba, and fomesafen, target-site mutations were the main underlying resistance mechanism (Baerson et al 2002;LeClere et al 2018;Wu et al 2020aWu et al , 2020bYu et al 2015). If NTR mechanisms such as reduced uptake and translocation are involved (Heap and Duke 2018;Sammons and Gaines 2014), the response of the resistant and sensitive plants at the chloroplast/PSII system level might be similar and thus prevent the leaf-disk assay from capturing their differences.…”
Section: Correlation Between F V /F M Values and Herbicide Spray Injuriesmentioning
confidence: 99%
“…A common practice to evaluate the spread of herbicide resistance is to do routine and massive surveys of weed populations from different geographic locations (Evans et al 2016;González-Torralva et al 2020;Westra et al 2019). These surveys have been done solely through time-consuming and labor-intensive greenhouse herbicide efficacy trials or a combination of greenhouse trials with molecular marker assays (Chatham et al 2015;Salas-Perez et al 2017;Schultz et al 2015;Varanasi et al 2018;Wu et al 2020a). A more rapid assay requiring fewer technical skills (e.g., molecular assays) will enable more weed science labs to conduct weed resistance surveys regularly and more efficiently.…”
Section: Introductionmentioning
confidence: 99%